Systematic review and updated recommendations for cardiomyopathy surveillance for survivors of childhood, adolescent, and young adult cancer from the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 3 (March 2023) - Ehrhardt, Matthew J; Leerink, Jan M; Mulder, Renée L; Mavinkurve-Groothuis, Annelies; Kok, Wouter; Nohria, Anju; Nathan, Paul C; Merkx, Remy; de Baat, Esmée; Asogwa, Ogechukwu A; Skinner, Roderick; Wallace, Hamish; et al.
Summary: Survivors of childhood, adolescent, and young adult cancer, previously treated with anthracycline chemotherapy (including mitoxantrone) or radiotherapy in which the heart was exposed, are at increased risk of cardiomyopathy. Symptomatic cardiomyopathy is typically preceded by a series of gradually progressive, asymptomatic changes in structure and function of the heart that can be ameliorated with treatment, prompting specialist organisations to endorse guidelines on cardiac surveillance in at-risk survivors of cancer. In 2015, the International Late Effects of Childhood Cancer Guideline Harmonization Group compiled these guidelines into a uniform set of recommendations applicable to a broad spectrum of clinical environments with varying resource availabilities. Since then, additional studies have provided insight into dose thresholds associated with a risk of asymptomatic and symptomatic cardiomyopathy, have characterised risk over time, and have established the cost-effectiveness of different surveillance strategies. This systematic Review and guideline provides updated recommendations based on the evidence published up to September, 2020.